Augmented Cognition c - Schmorrow, Dylan D.; Fidopiastis, Cali M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 16th International Conference on Augmented Cognition, AC 2022, held as part of the 23rd International Conference, HCI International 2022, which was held virtually in June/July 2022. The total of 1271 papers and 275 posters included in the HCII 2022 proceedings was carefully reviewed and selected from 5487 submissions. The AC 2022 proceedings aims to develop adaptive systems capable of extending the information management capacity of individuals through computing technologies and offers a broad range of theoretical and applied issues related to Augmented Cognition and its applications.
Understanding Human Cognition and Behavior -- Brain Activity Measurement and Electroencephalography -- Human and Machine Learning -- Extended Reality and Augmented Cognition.
Keywords: Artificial intelligence; 9; Social sciences -- Data processing; Pattern recognition systems; Computer vision; Computers; Artificial Intelligence; Computer Communication Networks; Computer Application in Social and Behavioral Sciences; Automated Pattern Recognition; Computer Vision; Computing Milieux